Faktor-Faktor yang Mempengaruhi Audit Delay dengan Spesialisasi Industri Auditor sebagai Pemoderasi - Ida Ayu Ratih Weda Dwijayani; Made Yenni Latrini (Universitas 17 Agustus 1945, 2024)
This study aims to empirically prove the influence of auditor switching, financial distress, and the complexity of company operations on audit delays and to prove empirically whether the specialization of the auditor industry moderates the influence of auditor switching, financial distress, and complexity of company operations on audit delays in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2019-2022. The population of this study is 167 companies. The sample was selected using the purposive sampling technique, so that a sample of 92 companies was obtained with observation for 4 years. The analysis technique used is Moderated Regression Analysis (MRA) or interaction test. The study obtained results that auditor switching, financial distress, and the complexity of company operations statistically have a positive and significant effect on audit delays, and the expertise of the auditor industry is able to moderate the influence of auditor switching, financial distress, and the complexity of company operations on audit delays.